2010
DOI: 10.1021/ja103354w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Substrate Shuttling by the Acyl-Carrier Protein within the Fatty Acid Mega-Synthase

Abstract: Fatty acid mega-synthases (FAS) are large complexes that integrate into a common protein scaffold all the enzymes required for the elongation of aliphatic chains. In fungi, FAS features two independent dome-shaped structures, each 3-fold symmetric, that serve as reaction chambers. Inside each chamber, three acyl-carrier proteins (ACP) are found double-tethered to the FAS scaffold by unstructured linkers; these are believed to shuttle the substrate among catalytic sites by a mechanism that is yet unknown. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 28 publications
3
53
1
6
Order By: Relevance
“…37 Extensive computer simulation work found that each ACP bounces stochastically within this chamber, but with asymmetric probability observed for multiple ACPs to simultaneously interact with equivalent catalytic sites. 38 The authors conclude this to be an entropic phenomenon and hesitate to suggest cooperativity between subunits. The yeast type I FAS (PDB: 3HMJ) 39 offers a similar barrel shape with a different domain arrangement, further studied by electron microscopy (EM).…”
Section: Fas Transport: Acpmentioning
confidence: 99%
“…37 Extensive computer simulation work found that each ACP bounces stochastically within this chamber, but with asymmetric probability observed for multiple ACPs to simultaneously interact with equivalent catalytic sites. 38 The authors conclude this to be an entropic phenomenon and hesitate to suggest cooperativity between subunits. The yeast type I FAS (PDB: 3HMJ) 39 offers a similar barrel shape with a different domain arrangement, further studied by electron microscopy (EM).…”
Section: Fas Transport: Acpmentioning
confidence: 99%
“…The fungal FAS is a highly efficient FA producing machinery that runs synthesis at higher turnover numbers than other type I FAS systems (18.2, 2.0 and 3.4 cycles per second; values per set of active sites calculated from specific activities reported for S. cerevisiae 10, Corynebacterium ammoniagenes 11 and chicken FAS12, respectively). The synthetic advantage of the fungal FAS lies in its highly developed architecture, in which the catalytic domains are embedded in an extensive scaffolding matrix, and substrate shuttling by the acyl carrier protein (ACP) is subtly balanced between electrostatic steering and molecular crowding properties131415 (Fig. 1a).…”
mentioning
confidence: 99%
“…This structural organization likely preserves linkers from interfering in ACP:domain interactions, and, concomitantly, may support the loading of the covalent acyl moiety by steering the acyl tail into the binding channels. A computational study, on the basis of S. cerevisiae FAS data, refined the understanding of ACP-mediated substrate shuttling in S. cerevisiae FAS by confirming steering in the sense of promoting correct orientations, as well as suggesting electrostatic steering by charge complementarity of the surfaces of binding partners [33]. Recent studies have characterized ACP of FAS megasynthases as not sequestering the covalently bound acyl moiety, which is supportive of molecular steering effects underlying substrate shuttling [3435].…”
Section: Reviewmentioning
confidence: 99%